DIGITAL PLATFORMS AS PROVISIONS FOR ENERGIZING ENTREPRENEURSHIP IN SPICY FOOD BUSINESSES - Zubaedah, Siti Yasmina; Yudi, Felicia; Caroline, Laura; Welly, Jocelyn (Graduate Program of Universitas Tarumanagara, 2025)
As prominent members of the developing digital entrepreneurial ecosystem in Indonesia, Micro-Small Enterprises (MSEs) should adapt and make the most out of the ubiquitous digital platforms available for managing business activities. Especially for those in the food business, digital marketing has played an important role to the development of MSEs performances. This research examines how spicy food MSEs are able to flourish without a formal marketing arm embedded in the organization. In particular, the main objectives of the study include to assess the role of digital marketing for MSEs and provide evidence on how adopting digital marketing would enhance entrepreneurial capabilities. Method employed for this study is a combination of three components, which are, preliminary desktop research, data mining, and descriptive analyses. Complementing quantitative and qualitative data from multiple sources was intended to overcome the challenges of obtaining MSE data by taking advantage of online databases and make use of available resources. Ratings provided by the users are determined to be representations for the MSEs performance, which are made available for the public. In addition, data shows the ability for MSEs to expand markets and access more customers using e-commerce platforms. Analyses presented in this article provide evidence of the vital role of adopting digital platforms in MSE marketing activities. Synergizing internal capabilities with the online ratings could snowball into obtaining good performance and sustainable competitive advantage. From an entrepreneurial point of view, analyses showed how digital marketing is the ultimate collaborative partner necessary for success.